2001
DOI: 10.1186/ar228
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of RA33 (hnRNP-A2/B1)-autoreactive T cells in SLE-patients

Abstract: We discuss the presence of anti-keratin antibodies (AKA) of the IgG class in patients with defined juvenile idiopathic arthritis (JIA). An indirect immunofluorescence test and rat oesophagus substrate was used for the detection and quantification of AKA antibodies in patients´ sera. Overall 33/60 patients with JIA had sera positive for AKA (55 %, P = 0,0001) ranging from 1:10 to 1:160 dilutions. Following idiopathic arthritis of childhood classification criteria AKA occurred in 2/7 patients with systemic disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Recently, we and another group reported preliminary findings describing the identification of human T cells reactive with hnRNP antigen (4,5). Fritsch and colleagues subsequently identified and studied hnRNPreactive T cells from patients with RA and reported that these T cells exhibited a Th1-like phenotype and were largely restricted in antigen recognition by HLA-DR molecules (6).…”
mentioning
confidence: 99%
“…Recently, we and another group reported preliminary findings describing the identification of human T cells reactive with hnRNP antigen (4,5). Fritsch and colleagues subsequently identified and studied hnRNPreactive T cells from patients with RA and reported that these T cells exhibited a Th1-like phenotype and were largely restricted in antigen recognition by HLA-DR molecules (6).…”
mentioning
confidence: 99%
“…Besides, autoreactive T cell clones against RA33 isolated from RA patients demonstrated an inclination toward Th1 phenotype with a strong production of IFN‐γ (Fritsch et al, 2002). Likewise, the PBMCs from SLE patients exhibited pronounced proliferative responses to hnRNP A2, and the T cell clones specific for hnRNP A2 encompassed high frequency of CD8 + CD28 − subsets which predominantly secreted interleukin (IL)‐10 (Fritsch‐Stork et al, 2006). In this regard, seeking ways that directly or indirectly hold down the aberrant expressions of hnRNPs or hnRNPs‐evoked immune responses may lead to therapeutic alternatives for specific autoimmune disorders, exemplified by the suppression of upregulated hnRNP A2/B1 in HDMECs induced via BD‐associated stimulants when treated with cilostazol (An et al, 2017).…”
Section: Hnrnps Are Autoantigens In Autoimmune Diseases and Associate...mentioning
confidence: 99%